Comparison of the single dose pharmacokinetics, pharmacodynamics, and safety of two novel oral formulations of dimethandrolone undecanoate (DMAU): a potential oral, male contraceptive. (1st December 2016) - Ayoub, R.; Page, S. T.; Swerdloff, R. S.; Liu, P. Y.; Amory, J. K.; Leung, A.; Hull, L.; Blithe, D.; Christy, A.; Chao, J. H.; Bremner, W. J.; Wang, C.
Summary: Dimethandrolone (DMA, 7α, 11β‐dimethyl‐19‐nortestosterone) has both androgenic and progestational activities, ideal properties for a male hormonal contraceptive. In vivo, dimethandrolone undecanoate (DMAU) is hydrolyzed to DMA. We showed previously that single oral doses of DMAU powder in capsule taken with food are well tolerated and effective at suppressing both LH and testosterone (T), but absorption was low. We compared the pharmacokinetics and pharmacodynamics of two new formulations of DMAU, in castor oil and in self‐emulsifying drug delivery systems (SEDDS), with the previously tested powder formulation. DMAU was dosed orally in healthy adult male volunteers at two academic medical centers. For each formulation tested in this double‐blind, placebo‐controlled study, 10 men received single, escalating, oral doses of DMAU (100, 200, and 400 mg) and two subjects received placebo. All doses were evaluated for both fasting and with a high fat meal. All three formulations were well tolerated without clinically significant changes in vital signs, blood counts, or serum chemistries. For all formulations, DMA and DMAU showed higher maximum ( p  < 0.007) and average concentrations ( p  < 0.002) at the 400 mg dose, compared with the 200 mg dose. The powder formulation resulted in a lower conversion of DMAU to DMA ( p  = 0.027) compared with both castor oil and SEDDS formulations. DMAU in SEDDS given fasting resulted in higher serum DMA and DMAU concentrations compared to the other two formulations. Serum LH and sex hormone concentrations were suppressed by all formulations of 200 and 400 mg DMAU when administered with food, but only the SEDDS formulation was effectively suppressed serum T when given fasting. We conclude that while all three formulations of oral DMAU are effective and well tolerated when administered with food, DMAU in oil and SEDDS increased conversion to DMA, and SEDDS may have some effectiveness when given fasting. These properties might be advantageous for the application of DMAU as a male contraceptive.